Analisis Pengaruh Kompensasi dan Lingkungan Kerja terhadap Semangat Kerja Karyawan KPN Eka Cita di Kec. Negara, Bali. - Nisa, Syaiva Hairun; Emilda, Emilda (Jurnal Nasional Manajemen Pemasaran dan SDM, 2023)
This study aims to analyze the influence of compensation and the work environment both simultaneously and partially and to analyze between compensation and the work environment which has the dominant influence on morale at KPN Eka Cita Negara. This research was conducted at KPN Eka Cita Negara with a sample of 30 employees. This research was conducted using primary data collected through the distribution of questionnaires which were given directly to the respondents. Furthermore, the data were analyzed using multiple linear regression analysis. The results of this study prove that compensation and work environment partially and simultaneously have a positive and significant effect on employee performance and compensation has a more dominant effect on morale at KPN Eka Cita Negara.